Palaeomagnetic evidence for the origin of the coastal flexure and dyke swarm in central E Greenland (Dataset) ... - A. M. Faller; N. J. Soper (Magnetics Information Consortium (MagIC), 2006)
Paleomagnetic, rock magnetic, or geomagnetic data found in the MagIC data repository from a paper titled: Palaeomagnetic evidence for the origin of the coastal flexure and dyke swarm in central E Greenland ...